Pragmatisme politik kaum elit - Nashir, Haedar (Yogyakarta : Pustaka Pelajar, 1999)
Pragmatic political leadership in Indonesia of the elite in power; collection of articles.
Includes bibliographical references (p. 193-196).
Mode of access: Internet.
Keywords: Political leadership -- Indonesia; Indonesia -- Politics and government -- 1966-1998.